2020
DOI: 10.4995/ijpme.2020.10817
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study of the business growth strategy related to the added value by intellectual capital

Abstract: <p class="TtuloAbstract">Four consecutive years of more than a thousand Spanish companies from different economic sectors are analyzed to determine the influence of intellectual capital on the business growth strategy. One of the purposes of this work is to establish a classification criterion of the strategic behaviour of a company linked to the growth of three factors: the demand of the sector, the sales of the company and the financial sustainability of the company. Another purpose is to develop and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…At the industry level, the market demand, sales growth and sustainable growth of each company in the supply chain defines the company's strategic behaviour in various categories (expansive, dominant, shrinking, restructuring, in decline and unfocused) that can be used to predict companies' profitability [23].…”
Section: Supply Chainmentioning
confidence: 99%
“…At the industry level, the market demand, sales growth and sustainable growth of each company in the supply chain defines the company's strategic behaviour in various categories (expansive, dominant, shrinking, restructuring, in decline and unfocused) that can be used to predict companies' profitability [23].…”
Section: Supply Chainmentioning
confidence: 99%
“…Further, the findings of Cheikh and Noubbigh (2019) showed that HC contributes the most to the market value of Tunisian listed firms. Analyzing 1,000 Spanish companies, Alcalde-Delgado et al (2020) found that there are inconsistent contributions to the value added of three IC components in different business life cycle. From the perspective of Polish SMEs, Gross-Gołacka et al (2020) showed that only HC has the greatest influence on business sustainability.…”
Section: Ic and Firm Performancementioning
confidence: 99%